The dynamic causality between money and macroeconomic activity:empirical evidence from Nigeria (1960-2011) - Olatunji, Tajudeen Mukhtar; Sunday, Adedokun Adebayo; Omolara, Yaqub Jameelah (Penerbit Universiti Kebangsaan Malaysia, 2012)

(untitled)
This paper examines the dynamic causality between money and macroeconomic activities (output, interest rate, exchange rate and prices) in Nigeria between 1960 and 2011. The methodologies applied include the multivariate cointegration test developed by Johansen (1988) and Johansen and Juselius (1990), the Granger causality test in vector error correction model (vEcm), impulse response function (JRF) and variance decomposition (vDc) method. The cointegration test indicates that a long run relationship exists among the macroeconomic variables. The VECM results show that, in the short-run, real GDP and money supply stand out econometrically exogenous, whereas the presence of causal relationships among the variables shows that money supply is not neutral in the short-run. There are unidirectional short-run relationships running from (I) broad money to price, (2) money supply to interest rate and (3) narrow money to exchange rate. The IRF indicates that a positive money shock would increase output and prices, while decreasing interest rates. The exchange rate, however, will remain relatively unchanged and stable for the first two years before decreasing. Considering the definitions of money stocks, broad money (M2) appears to have a stronger causal effect on real output than narrow money (M1). The VDCs show that money supply contains better information about the source of shocks that is affecting the economy when compared to others variables. This implies that money supply could be very useful for predicting the current and future growth rate in output and prices in the Nigerian economy. The Granger causal chain implies that the findings are consistent with the quantity theory of money as opposed to other economic paradigms. However, it also suggests that monetary policy alone is insufficient to achieve sustainable economic growth and price stability.